Using Deep Learning in a Monocentric Study to Characterize Maternal Immune Environment for Predicting Pregnancy Outcomes in the Recurrent Reproductive Failure Patients - Huang, Chunyu; Xiang, Zheng; Zhang, Yongnu; Tan, Dao Shen; Yip, Chun Kit; Liu, Zhiqiang; Li, Yuye; Yu, Shuyi; Diao, Lianghui; Wong, Lap Yan; Ling, Wai Lim; Zeng, Yong; et al. (Frontiers in Immunology, 2021)
Recurrent reproductive failure (RRF), such as recurrent pregnancy loss and repeated implantation failure, is characterized by complex etiologies and particularly associated with diverse maternal factors. It is currently believed that RRF is closely associated with the maternal environment, which is, in turn, affected by complex immune factors. Without the use of automated tools, it is often difficult to assess the interaction and synergistic effects of the various immune factors on the pregnancy outcome. As a result, the application of Artificial Intelligence (A.I.) has been explored in the field of assisted reproductive technology (ART). In this study, we reviewed studies on the use of A.I. to develop prediction models for pregnancy outcomes of patients who underwent ART treatment. A limited amount of models based on genetic markers or common indices have been established for prediction of pregnancy outcome of RRF patients. In this study, we applied A.I. to analyze the medical information of RRF patients, including immune indicators. The entire clinical samples set (561 samples) was divided into two sets: 90% of the set was used for training and 10% for testing. Different data panels were established to predict pregnancy outcomes at four different gestational nodes, including biochemical pregnancy, clinical pregnancy, on-going pregnancy, and live birth, respectively. The prediction models of pregnancy outcomes were established using sparse coding, based on six data panels: basic patient characteristics, hormone levels, autoantibodies, peripheral immunology, endometrial immunology as well as embryo parameters. The six data panels covered 64 variables. In terms of biochemical pregnancy prediction, the area-under-curve (AUC) using the endometrial immunology panel was the largest (AUC=0.766, Accuracy: 73.0%). The AUC using the autoantibodies panel was the largest in predicting clinical pregnancy (AUC=0.688, Accuracy: 78.4%), on-going pregnancy (AUC=0.802, Accuracy: 75.0%), and live birth (AUC=0.909, Accuracy: 89.7%). Combining the data panels did not enhance the effect on prediction of all the four pregnancy outcomes significantly. These results give us new insight on reproductive immunology and establish the basis for assisting clinicians to plan more precise and personalized diagnosis and treatment for RRF patients.